Processos culturalmente emancipatórios na práxis profissional do Serviço Social: uma problematização - Scabello, Juliana Cristina (2023)
Faced with the refractions of the neo-fascist and ultra-neoliberal conjuncture, the ideas and conceptions of the world of the ruling class still prevail over the subordinate classes in this capitalist sociability, infiltrating their social experiences as well as their consciousness and representations of reality. In this sense, this dissertation aims, in view of the research and bibliographical review of the theoretical framework of Social Work and related areas, to contribute to the theoretical reflection and possible strategies of professional practice of Social Work that favor the construction and strengthening of culturally emancipatory processes, mediated by art. To this end, it focused on the field of Social Service instrumentality in its ethical-political, theoretical-methodological and technical-operative dimensions, favoring the emancipatory pedagogical dimension, through the dialectical historical materialist method. Engendering culturally emancipatory processes in the professional practice of Social Work is about revealing the conflict between production and reproduction of social inequality and resistance and rebelliousness, contributing to the construction of new modes of existence and awareness of social reality in a more critical way, from an emancipatory perspective, through the construction of responses to the demands and social needs of the subjects in order to strengthen the struggle process and stimulate social participation in subaltern class movements that aim at a revolutionary transformation